The Transplantation and Replacement of Thoracic Organs The Present Status of Biological and Mechanical Replacement of the Heart and Lungs - Cooper, David K. C.; Miller, Leslie W.; Patterson, G. Alexander (Springer Netherlands, 1996)
It is a great pleasure for me to contribute a few words as an achieved by many heart transplant centers and the ever improving results of lung transplantation and the functioning of mechanical introduction to the second edition of this volume, first published in 1990 when it was edited by David Cooper and Dimitri cardiac assist devices. Novitzky. The first edition was, in fact, a greatly expanded The current editors bring a wealth of expertise and experience version of an even earlier volume Heart Transplantation, edited to their task, and have blended together absolutely superb con by David Cooper and Robert Lanza and published in 1984. This tributions by many of the world's experts in their fields. This first work, authored by members of the medical staff of Groote comprehensive and highly readable volume documents the Schuur Hospital and the University of Cape Town Medical present 'state of the art' in the field of transplantation and School, was, I believe, the first volume reviewing this relatively replacement of thoracic organs. It provides an invaluable and un new field of medicine. paralleled source of information for those concerned with heart and lung medicine or surgery, and is essential reading for all who The present volume, therefore, continues the documentation of wish to keep abreast of developments in this field